Faktor-Faktor Yang Mempengaruhi Konsumen Dalam Melakukan Pembelian Produk Waleu Kaos Lampung - lestari Wuryanti; Oktha Rizkiyawhan (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2020)
This study aims to determine and provide empirical evidence regarding the factors that influenceconsumers in purchasing Waleu Kaos Lampung Products. The independent variables in this study arelocation, service, and brand image, while the dependent variable is the purchase decision. Thisresearch is quantitative, the study population is Waleu consumers in Lampung. The sample wasdetermined based on probability sampling technique using the Slovin formula with a total of 89samples. The data obtained directly by distributing questionnaires in Waleu Lampung, while the dataanalysis technique used multiple analysis techniques.The results of this study concluded that locationhas no effect on purchasing decisions, while service and brand image influence purchasingdecisions.Based on the results of this study, it is suggested that the location variable (X1) gets thelowest score compared to other variables. This indicates that the road access to the Waleu Lampunglocation should be the focus considered in choosing an outlet location, in order to contribute topurchasing decisions.Keywords: Location, Service, Brand Image, Purchase Decision